Differential expression and regulation of MS4A family members in myeloid cells in physiological and pathological conditions. Issue 4 (4th August 2021) - Silva-Gomes, Rita; Mapelli, Sarah N; Boutet, Marie-Astrid; Mattiola, Irene; Sironi, Marina; Grizzi, Fabio; Colombo, Federico; Supino, Domenico; Carnevale, Silvia; Pasqualini, Fabio; Stravalaci, Matteo; Porte, Rémi; et al.
Abstract: The MS4A gene family encodes 18 tetraspanin-like proteins, most of which with unknown function. MS4A1 (CD20), MS4A2 (FcεRIβ), MS4A3 (HTm4), and MS4A4A play important roles in immunity, whereas expression and function of other members of the family are unknown. The present investigation was designed to obtain an expression fingerprint of MS4A family members, using bioinformatics analysis of public databases, RT-PCR, and protein analysis when possible. MS4A3, MS4A4A, MS4A4E, MS4A6A, MS4A7, and MS4A14 were expressed by myeloid cells. MS4A6A and MS4A14 were expressed in circulating monocytes and decreased during monocyte-to-Mϕ differentiation in parallel with an increase in MS4A4A expression. Analysis of gene expression regulation revealed a strong induction of MS4A4A, MS4A6A, MS4A7, and MS4A4E by glucocorticoid hormones. Consistently with in vitro findings, MS4A4A and MS4A7 were expressed in tissue Mϕs from COVID-19 and rheumatoid arthritis patients. Interestingly, MS4A3, selectively expressed in myeloid precursors, was found to be a marker of immature circulating neutrophils, a cellular population associated to COVID-19 severe disease. The results reported here show that members of the MS4A family are differentially expressed and regulated during myelomonocytic differentiation, and call for assessment of their functional role and value as therapeutic targets. Graphical Abstract: MS4A tetraspan molecules are differentially expressed and regulated in myeloid cells under normal and pathological conditions.